Nomenclature of Aushadh Sevan Kaal(Time of Drug Administration) In Various Ayurved Samhita’s and Its Commentaries- A Critical Review: Life Sciences -Ayurveda - S. Borkar, Dr. Preeti; Yanpallewar, Dr.Sushil; Pal Singh, Dr.Pratyendra; Pargaonkar, Dr. Akshay; Thakre, Dr.Rhushikesh (International Journal of Life Science and Pharma Research, 2023)
Aushadh Sevan Kaal is a concept described in Ayurved samhitas, which means the time of medicine administration.Kaal(Time) isincluded in karana dravya and plays many important roles in our lives. The existence of the Kaal is from the Shrishti Uttpatti.Aacharya charak hasdescribed Trisutra Ayurved, which explains the knowledge about the entire Ayurveda.Trisutra includes Hetu[causative factors], Linga[signs andsymptoms], and Aushadh [medicines]. Additional considerations listed by Acharya Charaka include the patient’s desha (region), kala (time),pramana (dosage), satmya (wholesomeness), asatmya (unwholesomeness), aahara (diet), and aushadh (medicine). Kaal is a particular and distinctcause of all kinds of outcomes and is also inevitable. Ayurveda is the science of life, emphasizing the idea of kaal as it is one of the karan dravya.The present study aims to critically analyze different terms used in samhitas for nomenclature and terminologies related to the administration time(aushadh sevan kaal) of ayurvedic herbo mineral formulations. To achieve this, we aim to study the concept of aushadha sevan kaal in varioussamhitas for its utility in identifying textual study material for selecting the treatment protocol. There are differences in the nomenclature[terminologies] in various samhitas and their commentaries. Mild variation is also observed in the number of types of Aushadh sevan kaal as perSamhitas. All Ayurveda treatments concentrate on maintaining and retaining the power of agni because it is the primary factor in establishing theDhatu Samyata.In the current era, it is observed that proper medicine administration needs to be done in relationship with Dosha,dusya,rogi, androgbala in consideration of the aushadh seven kaal. Hence, treatment is not successful in treating the patients.In this study, it is observed thatdifferent terms are mentioned in Ayurveda texts for different types of Aushadh sevan Kaal by different-different Acharyas.